Seismotektonik dan Potensi Kegempaan Wilayah Jawa - Soehaimi, A. (Geological Agency, 2008)
http://dx.doi.org/10.17014/ijog.vol3no4.20085A seismogenetic study shows the Jawa Island Arc and its subduction zone system belong to a highly active seismotectonic arc unit (west Jawa and Sumatera) and an active seismotectonic arc unit (western part of West Jawa â Central Jawa â East Jawa). In general, these regions are part of the Indonesian Earthquake Hazard Zones No. VI, VII, VII and IX. The regions are characterized by the presence of rare earthquake of magnitude > 8.5 Richter Scale (western part of Java), frequent magnitude of 7 Richter Scale and common 5 - 6 Richter Scale (Southern part of Java). The potential hazardous earthquake in Jawa that is > 5,6 Richter Scale of magnitude and shallow depth (< 30 km) is due to a subduction zone earthquake. Epicenter distance, magnitude, geological site conditions, population, and infrastructure are the index of earthquake hazard and risk in these regions. The earthquake hazard mitigation programme in the near future is a risk assesment based on macro and microzonation of earthquake hazard and risk. These macrozonation and microzonation assessments are essentially needed for provinces, districts, and cities. Â Â